The Irish in Bolivia: An (almost) Unknown History - Cruset, Maria Eugenia (2023)
Irish immigration to Bolivia has been largely ignored by academia. However, although few in number, it has exerted its infl uence both in the country itself and in the cause of Irish nationalism. Whether they arrived with General Bolívar’s liberating troops or collaborated in the development of the nation through their work in mining, commercial or railway companies, their con-tribution was signifi cant. Th ey were also important in the fi elds of culture, the press and domestic politics. Despite the political instability of the Andean country and the obstruction of the British Empire, they have left a mark that I intend to show in this article.Keywords: Bolivia, Diplomacy, Ireland, Nationalism, Politics1. IntroductionTh ere is a broad consensus in academia on the low level of interest within Irish studies towards the Diasporas which settled in the southern hemisphere. While of course the largest number of Irish went to North America (both United States and Cana-da) and the most signifi cant research and fi nancial resources are understandably devoted to that migration, it has led to decreased resources being devoted to other geographical areas of importance, notably Australia, New Zealand and, particularly, South America.Among recent academic publications we fi nd Tim Fanning’s workabout the nineteenth century (2017) and the extremely valuable volumes by Dermot Keogh (2016 and 2021). However, both authors being Irish inevitably means that their perspective is from the island of Ireland. I hope that my presentation will prove an incentive to other academics, from both north and the south, to delve deeper, perhaps also through collaborative work would of course be even more fruitful.